The Portuguese NHS 2024 reform: transformation through vertical integration - Goiana-da-Silva, Francisco; Sá, Juliana; Cabral, Miguel; Guedes, Raisa; Vasconcelos, Rafael; Sarmento, João; Morais Nunes, Alexandre; Moreira, Rita; Miraldo, Marisa; Ashrafian, Hutan; Darzi, Ara; Araújo, Fernando (Frontiers in Public Health, 2024)
Vertical integration models aim for the integration of services from different levels of care (e.g., primary, and secondary care) with the objective of increasing coordination and continuity of care as well as improving efficiency, quality, and access outcomes. This paper provides a view of the Portuguese National Health Service (NHS) healthcare providers' vertical integration, operationalized by the Portuguese NHS Executive Board during 2023 and 2024. This paper also aims to contribute to the discussion regarding the opportunities and constraints posed by public healthcare organizations vertical integration reforms. The Portuguese NHS operationalized the development and generalization of Local Health Units management model throughout the country. The same institutions are now responsible for both the primary care and the hospital care provided by public services in each geographic area, in an integrated manner. This 2024 reform also changed the NHS organic and organizational structures, opening paths to streamline the continuum of care. However, it will be important to ensure adequate monitoring and support, with the participation of healthcare services as well as community structures and other stakeholders, to promote an effective integration of care.